Direction of Capsular Strain Implies Surgical Repair Following Recurrent Anterior Shoulder Dislocation. Issue 7 (30th July 2018) - Takenaga, Tetsuya; Yoshida, Masahito; Chan, Calvin; Musahl, Volker; Lin, Albert; Debski, Richard
Objectives: Capsular plication is often performed in addition to arthroscopic Bankart repair. However, little is known regarding the direction of capsular injury making the direction of plication fairly arbitrary. This study aimed to determine the optimal direction for capsular plication within four sub-regions of the inferior glenohumeral capsule following multiple dislocations. Methods: Seven fresh-frozen cadaveric shoulders (age range 48-66 yrs) were dissected free of all soft tissue except the glenohumeral capsule. A grid of strain markers was affixed to the anterior and posterior band (A/PB) of the inferior glenohumeral ligament (IGHL), and the axillary pouch. The position of the markers while the capsule was inflated with minimal pressure served as the reference state. The humerus and scapula were then mounted in a 6 degree-of-freedom robotic testing system. At 60 degrees of abduction and 60 degrees of external rotation of the glenohumeral joint, an anterior load was applied to reach an anterior translation of one half the maximum AP width of the glenoid plus 10 mm. This definition of dislocation resulted in non-recoverable strain and a reproducible Bankart lesion. Following 1, 2, 3, 4, 5 and 10 dislocations, the positions of the strain markers were again recorded with the capsule inflated. The difference in these positions compared to the reference state defined the non-recoverable strain. The strain map was split into four sub-regions, the anterior band of IGHL (AB), anterior axillary pouch (AA), posterior axillary pouch (PA), and the posterior band of IGHL (PB) (Fig. 1). The angle of deviation between each of the maximum principle strain vectors and the AB-IGHL or PB-IGHL for the anterior and posterior regions of the capsule were determined using ImageJ. Circular statistics were employed to calculate mean direction of each sub-region and a Watson-Williams test was performed to compare mean direction among each dislocation with significance set at p < 0.05. The mean direction of all strain vectors in each sub-region was categorized as parallel or perpendicular to the AB-IGHL or PB-IGHL serving as the clinical reference. Direction ranging from 0 to 45 or 135 to 180 degrees was categorized as parallel. Direction ranging between 45 and 135 degrees was categorized as perpendicular. Results: The direction of 81.8% of the AB sub-regions was categorized as parallel and 18.2% categorized as perpendicular to the AB-IGHL. Direction of 61.3% of the AA sub-region was categorized as parallel (Table 1) and 38.7% categorized as perpendicular to AB-IGHL. The direction of 33.3% of the PA sub-region was categorized as parallel and 66.7% categorized as perpendicular to the PB-IGHL. The direction of 21.4% of PB sub-region was categorized as parallel and 78.6% categorized as perpendicular to PB-IGHL. A Watson-Williams test demonstrated that the direction of 81.3% of the sub-regions were not significantly different (p > 0.05) among dislocations for each specimen (Table 1). Conclusion: The non-recoverable strain in most of the AB and AP sub-regions were categorized as parallel to the AB-IGHL while for the PA and PB sub-regions mostly perpendicular to the PB-IGHL. These findings imply that it may be more optimal to plicate the anteroinferior capsule parallel to the AB-IGHL while posteroinferior capsular plication, which is often not classically considered for plication in the setting of anterior instability, may also be necessary and best performed perpendicular to the PB-IGHL. Figure 1. Fringe plot of non-recoverable strain for anterior half of inferior capsule in a typical shoulder following 5th dislocation. The borderline of AA and posterior axillary pouch sub-regions was the column of markers placed at the 6 o'clock position of the glenoid. AB-IGHL, anterior band of inferior glenohumeral ligament; AA, anterior axillary pouch sub-region; AB, anterior band of IGHL sub-region. Table 1. Direction of non-recoverable strain in the anterior axillary pouch sub-region following 1 st to 10 th dislocations for a typical shoulder (mean ± SD) Anterior Axillary Pouch sub-region Direction of non-recoverable strain Categorization Dislocation 1 168±5 Parallel to AB-IGHL Dislocation 2 168±8 Parallel to AB-IGHL Dislocation 3 166±5 Parallel to AB-IGHL Dislocation 4 165±5 Parallel to AB-IGHL Dislocation 5 175±13 Parallel to AB-IGHL Dislocation 10 158±20 Parallel to AB-IGHL Watson-Williams test showed directions were not significantly different among dislocation (p=0.33). Direction through 6 dislocation states were categorized as parallel (between 135 to 180 degrees) to anterior-band (AB) of IGHL